Harnessing Agricultural Trade for Sustainable Development: Guatemala - United Nations Conference on Trade; Development (United Nations, 2020)
This study is part of a series of UNCTAD publications that focus on policies in three countries, Guatemala, Vanuatu and Malawi, aimed at upgrading and diversifying specific agricultural sectors of rural economies in developing countries with a view to raising living standards among small-scale farmers in a context of female empowerment and food security and above all, sustainable development. The study analyses three agricultural sectors in Guatemala – potato, cocoa and cardamom - in terms of opportunities derived from trade of primary and processed products. The focus is on the growing trend among consumers in high income countries for artisanal, fair-trade, organically grown, single-origin products that allow niche market penetration by integrating into their traded products a narrative on the history and lives of local farming communities where the primary product is cultivated. The study bears in mind the heavy costs to implement Voluntary Sustainable Standards, internationally-accepted certification systems, or consumer-driven specific standards set by retailers, looking at domestic sales opportunities, for example within Guatemala’s growing tourism sector, which also allows farmers to hedge against price fluctuations in international markets. According to the study’s sustainability analysis, the strategies presented are aligned with sustainable development goals, integrating environmental, social welfare, gender equality, a more equitable distribution of income, and, more diversified income opportunities. Outcomes are expected to be positive overall, but the study nevertheless advises care in implementation to minimise any unforeseen and potentially negative long-term impacts, for example on issues such as staple food production. It further cautions on possible perverse consequences whereby, without successfully integrating small-scale farmers in the product value-chain, the strategies’ principal beneficiaries may rather be intermediaries. This report concludes with a set of recommended sustainable development policies that take into account food security and the importance of agriculture not only for small-scale farmers but for Guatemala’s economy as a whole.